2019
DOI: 10.1080/13543784.2019.1583742
|View full text |Cite
|
Sign up to set email alerts
|

RX-3117 (fluorocyclopentenyl cytosine): a novel specific antimetabolite for selective cancer treatment

Abstract: Introduction: RX-3117 is an oral, small molecule cytidine analog anticancer agent with an improved pharmacological profile relative to gemcitabine and other nucleoside analogs. The agent has excellent activity against various cancer cell lines and xenografts including gemcitabine-resistant variants and it has excellent oral bioavailability; it is not a substrate for the degradation enzyme cytidine deaminase. RX-3117 is being evaluated at a daily oral schedule of 700 mg (5 days/week for 3 weeks) which results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Since hypermethylation of TSGs is cell line dependent we chose A549 cells to study the effect of RX-3117 on protein expression of O-6-methylguanine-DNA methyltransferase (MGMT) and E-cadherin, while SW1573 cells were chosen to study the effect on p16. Earlier we demonstrated a concentration and time-dependent down-regulation of DNMT1 in cell lines with various histological backgrounds (NSCLC, ovarian cancer, pancreatic cancer, breast cancer) [1,3,4].…”
Section: Targeting Dna Methylationmentioning
confidence: 84%
See 1 more Smart Citation
“…Since hypermethylation of TSGs is cell line dependent we chose A549 cells to study the effect of RX-3117 on protein expression of O-6-methylguanine-DNA methyltransferase (MGMT) and E-cadherin, while SW1573 cells were chosen to study the effect on p16. Earlier we demonstrated a concentration and time-dependent down-regulation of DNMT1 in cell lines with various histological backgrounds (NSCLC, ovarian cancer, pancreatic cancer, breast cancer) [1,3,4].…”
Section: Targeting Dna Methylationmentioning
confidence: 84%
“…RX-3117 is a novel cytidine analog modified in the sugar ring moiety [1] (Figure 1), which has shown promising anti-tumor activity against gemcitabine resistant xenografts from different pathologies [2] and is currently in clinical trial (NCT02030067) [3]. RX-3117 was shown to down-regulate DNA methyl transferase 1 (DNMT1) [1,[3][4][5][6]. The pharmacological consequences of this inhibition, however, have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, global deprotection was achieved by sequential treatment with methanolic ammonia and BBr 3 , providing uracil derivate 85 which was converted to 76 via a standard four-step process. Of the four nucleoside analogues evaluated (Figure 8), derivative 76 showed significant potency against several human cancer cell lines (Table 3) [51,54,55]. Furthermore, Jeong reported that 76 also showed significant antitumour activity in a nude mouse xenograft model implanted with A549 human lung cancer cells, wherein after 38 days the inhibition of tumour growth was 32% and 58% at 3 and 10 mg/kg doses, respectively [54].…”
Section: Carbocyclic Nucleosidesmentioning
confidence: 99%
“…RX-3117 (fluorocyclopentenylcytosine) is a novel cytidine analogue with a modified ribose molecule [ 89 ]. To be incorporated into DNA or RNA, the RX-3117 molecule is firstly activated through transformation into a triphosphate form by uridine–cytidine kinase 2 [ 90 ]. Although RX-3117 is not a substrate for cytidine deaminase [ 89 ], other enzymes such as NT5C3 may have a role in breaking an intermediate monophosphate form, resulting in RX-3117 inactivation [ 90 ].…”
Section: Dnmt Inhibitorsmentioning
confidence: 99%
“…To be incorporated into DNA or RNA, the RX-3117 molecule is firstly activated through transformation into a triphosphate form by uridine–cytidine kinase 2 [ 90 ]. Although RX-3117 is not a substrate for cytidine deaminase [ 89 ], other enzymes such as NT5C3 may have a role in breaking an intermediate monophosphate form, resulting in RX-3117 inactivation [ 90 ]. RX-3117′s anti-tumor effects were evaluated in nine different xenograft mouse models and showed promise for the treatment of tumors that are sensitive and resistant to gemcitabine [ 91 ].…”
Section: Dnmt Inhibitorsmentioning
confidence: 99%